Sustaining containment of COVID-19: global sharing for pandemic response - Mitsuya, Hiroaki; Kokudo, Norihiro (Global Health & Medicine, 2020)
The coronavirus disease 2019 (COVID-19) outbreak, caused by SARS-CoV-2, has rapidly escalated into a global pandemic. One of our significant concerns is that we have no data as to whether people, who acquired immunity against this deadly virus and recovered from COVID-19, are protected from further infections with the same virus. Moreover, we have no data as to whether this pandemic will persist in our societies and continue vexing us for long periods of time. Implementing science-based response strategy is essential to sustain containment of COVID-19 globally. Rapidly sharing scientific information means providing real-time research data and relevant findings. As an international academic journal, Global Health & Medicine publishes this special issue entitled "GHM Special Topic: COVID-19". It includes a range of articles describing COVID-19 based on frontline data from Japan, China, the United States, Italy, the United Kingdom, and other countries and areas worldwide. Our hope is that the rapid publication and sharing of information contribute, in whichever possible way, to this global fight against COVID-19.